Traumatic Atlanto-Axial Rotatory Fixation. Issue 1 (24th January 2022) - Can, Damla; Duran, Unal; Dondelinger, Robert Ferdinand
Teaching point: In atlanto-axial rotatory fixation, CT in neutral position typically shows rotation of C1 on C2. Upon head rotation, atlas and axis rotate as one unit.